PRINCIPALS’ APPLICATION OF VIDEO SURVEILLANCE CAMERAS AS SECURITY MANAGEMENT PRACTICES IN THE ADMINISTRATION OF SECONDARY SCHOOLS IN ENUGU STATE - Ene, Gloria Ukamaka (Journal of Continuing and Development Education, 2023)
This study investigated principals’ application of video surveillance, camera as security management practices in the administration of secondary schools in Enugu state. The study adopted descriptive survey design. The population for the study was 8,816 respondents. It comprised 295 principals and 8,521 teachers in the public secondary schools in Enugu state. The sample size of the study consists of 338 respondents, consisting of 47 principals and 291 teachers in Enugu state public secondary schools, as at the time of this study. The instrument for data collection was a structured questionnaire which contained 5 items. The instrument was faced-validated by three experts; one from the Department of Mathematics and Computer Education and two from Department of Educational Management; all from the Faculty of Education, Enugu State University of Science and Technology (ESUT). The reliability of the instrument was determined using Cronbach alpha and overall reliability coefficient of 0.95 was obtained, which indicates that the instrument was reliable and therefore, considered appropriate for data collection. Hypotheses were tested at.05 level of significance. The questionnaires were administered to the respondents by the researcher with the help of five research assistants who were briefed on the method of administering and retrieving of the instruments. Statistical tools used for data analysis for the study were Mean, Standard Deviation and t-test statistics, The findings revealed that the extent to which principals, use video surveillance cameras, as security management practice is to a low extent. Based on the findings, it was recommended among others that, the governments through the federal, state Ministries of Education and the Post Primary School Management Board (PPSMB) should organize workshops and seminars that will expose principals on the latest technological tools such as video surveillance, cameras for ensuring security in their schools.